Assessment of patient satisfaction with primary health care - Krzeminska, Sylwia; Paszkowska, Aneta; Polanowska, Marta (Journal of Education, Health and Sport, 2025)
Introduction: Primary health care (PHC) is a key element of the healthcare system, serving as the first point of contact in medicine and providing access to early diagnostics, prevention, and patient qualification for further treatment. Methodology: To assess satisfaction, a diagnostic survey method with a questionnaire technique was used, employing an original questionnaire containing 24 closed questions and one open question. The questionnaires were handed to patients after using PHC services. The analysis included surveys from 140 individuals (55% women, 45% men; the largest group of patients was aged 41-60 years (35%); 45% had secondary education). Results: Reasons for choosing the practice: mainly proximity to place of residence (64.3%) and good opinion of family/friends (55%), waiting time for an appointment (25.7%). Evaluation of service availability: telephone registration was often rated as average (47.9%), availability of tests and referrals mostly rated good or very good. Premises conditions: 77.8% rated them as good or very good. Information on Patient Rights was available in 63.6% of clinics, and 45% of patients confirmed compliance with these rights. Satisfaction level: 42.1% of patients declared an average level, 38.6% high, 19.3% low. Conclusions: The main motives for choosing a PHC facility are proximity to the place of residence and positive opinion of the environment. Most patients are satisfied with the quality of services provided, but older people (over 60 years) report significantly lower satisfaction levels. A key role in building satisfaction is played by the method of conveying information and the quality of nursing care. Reducing waiting time for an appointment significantly increases patient satisfaction. Regular measurement of patient satisfaction should be a permanent element of quality management in primary health care.